Development of Micro, Small and Medium Enterprises (MSMEs) Based on Local Wisdom to Enhance Community Welfare in West Kalimantan's Border Region - Rini Yayuk Priyati; Sari; Dio Bimo Saputro (Equator Journal of Management and Entrepreneurship (EJME), 2026)
This study analyzes the creative economy development strategy of MSMEs based on local wisdom to improve the welfare of communities in the border area of Sambas Regency, West Kalimantan. The research focuses on rattan craft MSMEs in Piantus Village, Sejangkung District, an area known for its strong cultural and natural resource potential, which unfortunately remains underutilized. Piantus Village has a rattan weaving tradition passed down through generations, but its development has tended to stagnate due to various internal and external constraints. This study employed qualitative methods, incorporating data collection techniques like field observations, in-depth interviews, and focus group discussions with rattan craftsmen, cooperative administrators, village officials, and relevant government agencies. The results show that the development of rattan craft MSMEs in Piantus Village is hindered by a shortage of high-quality rattan raw materials, a lack of innovative products, and insufficient regeneration of young craftsmen willing to carry on this traditional trade. Marketing processes are still being conducted in a traditional manner, which leads to a limited market reach and an inability to keep up with the changing dynamics of modern market demand. Government support in various forms, including training, equipment assistance, exhibition facilities, and access to capital through the People's Business Credit (KUR), has not been fully implemented effectively. Most artisans still view rattan craft businesses as a sideline, which makes them hesitant to take risks to innovate or enhance product quality. This study suggests several development strategies based on its findings, including enhancing human resource capacity by using the Rattan Small and Medium Enterprises Center (Sentra IKM Rattan) as a training facility, fostering business partnerships with the furniture industry to broaden the supply chain, establishing regulations between middlemen to ensure consistent prices and product quality, and introducing the "1 Village 1 CEO" management model to improve more professional MSME business management. It is hoped that rattan craft MSMEs in Piantus Village can develop sustainably and make a greater contribution to enhancing the welfare of border communities. Keywords: MSMEs, Creative Economy, Local Wisdom, Rattan Crafts